2001
DOI: 10.1074/jbc.m104873200
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin Restores a Defective Heat Shock Responsein Vivo

Abstract: Induced expression of heat shock proteins (Hsps) plays a central role in promoting cellular survival after environmental and physiological stress. We have previously shown that scrapie-infected mouse neuroblastoma (ScN2a) cells fail to induce the expression of Hsp72 and Hsp28 after various stress conditions. Here we present evidence that this impaired stress response is due to an altered regulation of HSF1 activity. Upon stress in ScN2a cells, HSF1 was converted into hyperphosphorylated trimers but failed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 66 publications
4
48
0
Order By: Relevance
“…Previous studies have shown that Hsp27 is highly up-regulated after treatment of cells with Hsp90-directed agents such as 17-AAG (10,12). This prompted us to hypothesize that up-regulation of Hsp27 would decrease 17-AAG cell sensitivity and contribute to 17-AAG resistance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that Hsp27 is highly up-regulated after treatment of cells with Hsp90-directed agents such as 17-AAG (10,12). This prompted us to hypothesize that up-regulation of Hsp27 would decrease 17-AAG cell sensitivity and contribute to 17-AAG resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Because these proteins are dramatically up-regulated in response to treatment with Hsp90 inhibitors such as GA or 17-AAG (10)(11)(12), their potential involvement in resistance to Hsp90 inhibitors in the clinic has recently gained interest (16). Other studies have shown the protection of cancer cells from 17-AAG-induced death by Hsp70, which is known to be up-regulated in response to Hsp90-directed agents (17).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yeast cells were transformed using the LiCl method (36,37). N2a cells were transfected using the LipofectAMINE Plus reagent (Invitrogen) as described previously (38).…”
Section: Methodsmentioning
confidence: 99%